An investigation of TIG welding parameters on microhardness and microstructure of heat affected zone of HSLA steel - Musa, Mukhtaruddin Iqbal A.; Maleque, Md. Abdul; Ali, Mohammad Yeakub (IOP Publishing, 2018)
Nowadays a wide variety of metal joining methods are used in fabrication industries. In this study, the effect of various welding parameters of the TIG welding process on microhardness, depth, and microstructure of the heat-affected zone (HAZ) of L450 HSLA steel and optimizing these process parameters following Taguchi experimental design was investigated. The microhardness tended to increase significantly with the increase of welding speed from 1.0 to 2.5 mm/s whereas the width of HAZ decreased. The current and arc voltage was found to be less significant in relative comparison. Microstructures of the welded samples were also studied to analyze the changes in the microstructure of the material in terms of ferrite, pearlite, bainite, and martensite formations. Welding speed was found to be the most significant factors leading to changes in microhardness and metallurgical properties. The increase of welding heat input caused an increase in width (depth) of HAZ and the growth of prior austenite grains and then enlarged the grain size of coarse grain heat affected zone (CGHAZ). However, the amount of martensite in the HAZ decreased accompanied by an opposite change of paint. It was observed that the hardness properties and the microstructural feature of HAZ area was strongly affected by the welding parameters.